2022
DOI: 10.3389/fsufs.2021.822263
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Indicators for Sustainable Healthy Diets

Abstract: Introduction: Diets are currently unsustainable in many countries as evidenced by the growing burden of malnutrition, degradation of natural resources, contributions to climate change, and unaffordability of healthy diets. Agreement on what constitutes a healthy and sustainable diet has been debated. In 2019, FAO and WHO published the Sustainable Healthy Diets Guiding Principles, defining what qualifies as a sustainable healthy diet. While valuable, these principles require measurable indicators to support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 93 publications
1
15
0
1
Order By: Relevance
“…74 In addition, our review provides a summary of the most common outcome measures to assess the effectiveness of double-and tripleduty actions. In line with Harrison et al's review on indicators for evaluating sustainable healthy diets, 75 we found that the most frequently reported outcomes were changes in dietary intake, diet composition, greenhouse gas emissions, and food waste. We extend this knowledge by identifying further outcome measures that include changes in food and environmental sustainability-related attitudes and knowledge, changes in the nutritional quality and environmental sustainability of school food purchases, changes in the frequency of active travel, and changes in mortality and other health-related outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…74 In addition, our review provides a summary of the most common outcome measures to assess the effectiveness of double-and tripleduty actions. In line with Harrison et al's review on indicators for evaluating sustainable healthy diets, 75 we found that the most frequently reported outcomes were changes in dietary intake, diet composition, greenhouse gas emissions, and food waste. We extend this knowledge by identifying further outcome measures that include changes in food and environmental sustainability-related attitudes and knowledge, changes in the nutritional quality and environmental sustainability of school food purchases, changes in the frequency of active travel, and changes in mortality and other health-related outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The concept of territorial diets informs several metric developments, as shown in this review, but other sociocultural aspects have not yet been considered. Indicators of affordability and cultural acceptability of diets have been proposed [ 28 ]. However, evidence of inclusion of these indicators in dietary metrics and development of indicators for desirability and adverse sex-related effects are still lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indicators of affordability and cultural acceptability of diets have been proposed [ 28 ]. However, evidence of inclusion of these indicators in dietary metrics and development of indicators for desirability and adverse sex-related effects are still lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The principles of sustainable healthy diets are set to provide flexible roadmaps for policy actors [ 100 ]. On the other hand, for a sustainable and healthy diet to be quantified, the dimensions selected for each index require meticulous assessment by relevant indicators [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Eme [ 102 ], and as demonstrated in the present review, the evidence basis for selecting specific and robust indicators for sustainable diet indexes is frequently weak, fragmented, and arbitrary. Furthermore, great heterogeneity is apparent among the included indicators and their weight on population health [ 100 ]. Many indexes do not adequately account for the diets’ environmental impact, whereas others fall short in the economic impact domain.…”
Section: Discussionmentioning
confidence: 99%